Bildung antiborghese e individuazione in Ahnung und Gegenwart e Aus dem Leben eines Taugenichts di Joseph von Eichendorff (ENTHYMEMA, 2021)
The paper aims at advancing an interpretation of two works by Joseph von Eichendorff: Ahnung und Gegenwart (1815) and Aus dem Leben eines Taugenichts (1826). Francesco Orlando’s theory of literature is used to demonstrate that in both texts the phenomenon of Romantic anticapitalism finds expression in the return of repressed contents embodied by the protagonists of the texts under investigation: Friedrich, a medieval-like knight, and a good-for-nothing rebelling against the performance principle. Both characters experience a Bildung, which, in the case of the novella Aus dem Leben eines Taugenichts, takes on the form of an individuation process that is characterized by the emergence of archetypical images and that may be reconstructed by means of Jungian concepts. Freud’s psychoanalysis and Jung’s analytical psychology are therefore employed to focus on the antimodern identity of these characters and the features that differentiate the good-for-nothing’s Bildungsweg from Friedrich’s process of inner development.Keywords: Joseph von Eichendorff, Ahnung und Gegenwart, Aus dem Leben eines Taugenichts, Francesco Orlando, C. G. Jung.
Keywords: Keywords: Joseph von Eichendorff, Ahnung und Gegenwart, Aus dem Leben eines Taugenichts, Francesco Orlando, C. G. Jung.